2012
DOI: 10.1371/journal.pone.0052030
|View full text |Cite
|
Sign up to set email alerts
|

The Rice R2R3-MYB Transcription Factor OsMYB55 Is Involved in the Tolerance to High Temperature and Modulates Amino Acid Metabolism

Abstract: Temperatures higher than the optimum negatively affects plant growth and development. Tolerance to high temperature is a complex process that involves several pathways. Understanding this process, especially in crops such as rice, is essential to prepare for predicted climate changes due to global warming. Here, we show that OsMYB55 is induced by high temperature and overexpression of OsMYB55 resulted in improved plant growth under high temperature and decreased the negative effect of high temperature on grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(104 citation statements)
references
References 54 publications
5
98
0
1
Order By: Relevance
“…Similarly, El-kereamy et al (2012) studied the rice R2R3-MYB transcription factor OsMYB55 and concluded that overexpression of OsMYB55 improved rice plant tolerance to high temperature which was associated with enhanced amino acid metabolism through transcription activation. Liao et al (2008) identified 156 GmMYB genes in soyabean (Glycine max) of which the expression of 43 genes changed on treatment with ABA, salt, drought and/or cold stress.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…Similarly, El-kereamy et al (2012) studied the rice R2R3-MYB transcription factor OsMYB55 and concluded that overexpression of OsMYB55 improved rice plant tolerance to high temperature which was associated with enhanced amino acid metabolism through transcription activation. Liao et al (2008) identified 156 GmMYB genes in soyabean (Glycine max) of which the expression of 43 genes changed on treatment with ABA, salt, drought and/or cold stress.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…In warm day-and cool night-induced spikes, specific transcription factors encoding NAC, MYB and ARF proteins were obtained. These proteins also participated in flower organ development (Sablowski and Meyerowitz, 1998), amino acid metabolism (ElKereamy et al, 2012), flavonoid biosynthesis (Nakatsuka et al, 2012), and red fruit-flesh phenotypes (Chagné et al, 2013), as well as response to different biotic and abiotic stresses (El-Kereamy et al, 2012;Li et al, 2012b). Compared with the expression levels in juvenile apical leaves, the accumulated transcripts of NAC (FS449) and R2R3-like MYB (FS789) were higher in all spikes tested, while the accumulated transcripts of ARF (FS899) were lower in early and later stages of spikes (Figure 1).…”
Section: Genes Involved In Transcriptional Regulationmentioning
confidence: 99%
“…OsMYB1R1 is the first rice MYB family gene identified to function in flowering time MYB TFs in rice mainly function in biotic and abiotic stress [43][44][45][46][47][48], secondary wall biosynthesis [49,50], . Tissue-specific expression patterns of OsMYB1R1 (means AE SD, n = 3).…”
Section: Discussionmentioning
confidence: 99%